2022
DOI: 10.1049/cit2.12074
|View full text |Cite
|
Sign up to set email alerts
|

Research on image sentiment analysis technology based on sparse representation

Abstract: Many methods based on deep learning have achieved amazing results in image sentiment analysis. However, these existing methods usually pursue high accuracy, ignoring the effect on model training efficiency. Considering that when faced with large‐scale sentiment analysis tasks, the high accuracy rate often requires long experimental time. In view of the weakness, a method that can greatly improve experimental efficiency with only small fluctuations in model accuracy is proposed, and singular value decomposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The sparse representation by singular vector decomposition is used to enhance the efficiency of deep learning in image sentiment analysis. It ignores the local smoothness assumption as an effective prior knowledge 31 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The sparse representation by singular vector decomposition is used to enhance the efficiency of deep learning in image sentiment analysis. It ignores the local smoothness assumption as an effective prior knowledge 31 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sparse representation has led to promising results in a wide range of applications, including visual recognition 27 , image synthesis 28 , animation 29 , denoising 30 , etc. Recently, sparse representation is applied to sentiment analysis 31 , 32 . -norm sparsity is exploited to represent micro-videos with the aim of finding the main frame including sentiment 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional methods mathematically model the relationship between LR HS image, HR RGB image and HR HS image, concentrate the prior exploitation of the desired HR HS image, for example, sparse representation [36, 37]. Matrix factorisation (MF) is the most popular technique employed by traditional methods [13–17, 38, 39].…”
Section: Related Workmentioning
confidence: 99%
“…The third article researches different types of feature selection methods, considering various sparse learning algorithms, followed by a novel fast classification method for fine grained emotion recognition tasks [3]. The authors confirmed that, using this faster dictionary learning algorithm, the convergence of the network model is accelerated, and a better balance between classification efficiency and classification quality is achieved.…”
mentioning
confidence: 97%